PENGARUH PEMBERIAN KOMPOS KULIT BUAH KAKAO TERHADAP PERTUMBUHAN BIBIT TANAMAN KARET (Hevea brasiliensis Muell Arg.) STUM MINI KLON PB 260 - Fitri Haryati; Syafrinal Syafrinal (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of cacao rind compost and to obtain the best dose on the growth of seedlings of mini stum rubber plant clones PB 260. This study has been conducted in the experimental garden of Agriculture faculty, University of Riau from May 2016 until August 2016. The research has conducted experimentally by using Completely Randomized Design with single factor which is the giving of rind compost with the dose of A0: 0 g/polybag,      A1: 50 g/polybag, A2; 100 g/polybag, A3: 150 g/polybag, A4: 200 g/polybag. The observation parameters were; the increase of plant height, the increase of leaf number, the increase of stem diameter, the leaf wide. The obtained result were then analyzed using the variance and tested further by using Duncan's New Multiple Range Test (DNMRT) at 5% level test. The results showed that the compost of cocoa peel on seeds of mini stum rubber plant clone PB 260 were effected to the increase of seedling height, the increase of leaf number, the increase of  stem diameter, and the wide leaf area. The results of this study showed that the composting of cocoa peel on the rubber seedlings stum mini clone PB 260 with dose 200  g/polybag  which gives the best result that can be seen from the increase of seedling height, the increase of leaf number, the stem diameter and the leaf wide.Keyword : cocoa rind compost, seedling  rubber.